Evaluation of Potential Protective Factors Against Metabolic Syndrome in Bottlenose Dolphins: Feeding and Activity Patterns of Dolphins in Sarasota Bay, Florida - Wells, Randall; McHugh, Katherine A.; Douglas, David C.; Shippee, Steve; Berens McCabe, Elizabeth J.; Barros, Nelio B.; Phillips, Goldie T. (Frontiers in Endocrinology, 2013)
Free-ranging bottlenose dolphins (Tursiops truncatus) living in Sarasota Bay, Florida appear to have a lower risk of developing insulin resistance and metabolic syndrome compared to a group of dolphins managed under human care. Similar to humans, differences in diet and activity cycles between these groups may explain why Sarasota dolphins have lower insulin, glucose, and lipids. To identify potential protective factors against metabolic syndrome, existing and new data were incorporated to describe feeding and activity patterns of the Sarasota Bay wild dolphin community. Sarasota dolphins eat a wide variety of live fish and spend 10-20% of daylight hours foraging and feeding. Feeding occurs throughout the day, with the dolphins eating small proportions of their total daily intake in brief bouts. The natural pattern of wild dolphins is to feed as necessary and possible at any time of the day or night. Wild dolphins rarely eat dead fish or consume large amounts of prey in concentrated time periods. Wild dolphins are active throughout the day and night; they may engage in bouts of each key activity category at any time during daytime. Dive patterns of radio-tagged dolphins varied only slightly with time of day. Travel rates may be slightly lower at night, suggesting a diurnal rhythm, albeit not one involving complete, extended rest. In comparison, the managed dolphins are older; often fed a smaller variety of frozen-thawed fish types; fed fish species not in their natural diet; feedings and engaged activities are often during the day; and they are fed larger but fewer meals. In summary, potential protective factors against metabolic syndrome in dolphins may include young age, activity and small meals fed throughout the day and night, and specific fish nutrients. These protective factors against insulin resistance and type 2 diabetes are similar to those reported in humans. Further studies may benefit humans and dolphins.